BELAJAR BERSAMA COVID 19: Evaluasi Pembelajaran Daring Era Pandemi di Perguruan Tinggi Keagamaan Islam Negeri, Papua Barat - Agus Yudiawan (Al-Fikr: Jurnal Pendidikan Islam, 2020)
This research aims to encourage the implementation of bold learning in the State Islamic HigherEducation since the COVID-19 outbreak. The research method uses the CIPP evaluation model developed by Stufflebeam. The number of samples is set at 263 at a 5% margin of error. Data was collected through an open survey technique with a questionnaire-assisted instrument form Google. Analysis data is used as a quantitative descriptive. The results of the study showed that the implementation of bold learning had been carried out well amid the co-19 pandemic. Contextindicators, inputs, processes, and average production are in a good category. Interesting finding students as learning objects of financial difficulties in fulfilling network access. The conclusion is a bold learning model that is quite effective and can be used as a learning medium accompanied byPandemic. In addition, as an agreement, an immediate policy on education costs must be carried out which is the impact of COVID-19.